The "Lord Cooke Project": Reviewing Lord Cooke's Extrajudicial Writing - Cochrane, Tim; Chan, Elizabeth (Victoria University of Wellington Law Review, 2013)
This note discusses key themes arising from Lord Cooke's published extrajudicial writing. These themes cover Lord Cooke's conception of the common law, the interpretation of the Treaty of Waitangi, the development of bill of rights jurisprudence in New Zealand and overseas, and the role of judges. This note arises out of the authors' involvement in the Lord Cooke project, a Victoria University of Wellington initiative that will make a complete collection of Lord Cooke's extrajudicial writings available online.